A particle model on an unstructured mesh - Kazeminezhad, F.; Zalesak, S.; Spicer, D. (Computer physics communications, 1995)
We describe a particle in the cell scheme which incorporates finite elements in space and finite difference in time to follow the trajectories of particles in their self consistent fields. As such the model exploits the power of finite element techniques to better investigate the rich physics embedded in the particle or kinetic models. A brief description of the foundations of the hybrid model of kinetic ions and mass-less fluid electrons is first presented, followed by a brief summary of linear finite elements on triangles with relevance to the particle modeling. The particle trace method on triangular elements, particle to node density assignment, node to particle response, the scheme algorithm, numerical stability, and finally tests of the code via eigenmode analysis and comparison with the analytic theory and the structured simulation results are presented. The version presented here is a 2 1 2- dimensional one.